Variaciones mensuales en el aporte de biomasa al suelo por distintas especies de matorral mediterráneo - Lavado M.; Nuñez E.; Escudero J.C. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The annual production of dead leaves along with the monthly and seasonal fluctuations in the contribution of biomass to the ground have been quantitatively determined in two species of Mediterranean maquis: Myrtus communis L. and Pistacia lentiscus L. The total dead leaf contribution to the ground is 1,206.34 Kg/ha/year in M. communis, the leaves representing 70-74 per cent; in P. lentiscus 2,364.81 Kg/ha/year, the leaves making up 72-79 per cent, with the stem fraction accounting for an important part of the contribution which represents 25-28 per cent of the yearly total of dead leaves in P. lentiscus and 25-30 per cent in M. communis.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)